The effects of different levels of mesquite (Prosopis chilensis) pods on the performance of Shugor lambs in Halfa Elgadeda, Kassala State, Sudan - A. B. Osman, Amani; E. Elimam, Mohmed (Gezira Journal of Agricultural Science, 2023)
SHORT NOTE    Sheep production is very important in the Sudan due to high population, wide distribution and contribution to self sufficiency and meat exports. The demand for Sudanese sheep meat is increasing as they depend on natural pastures with no feed additives or growth promoters affecting human and animal health. Nutrition is one of the main constraints for sheep production due to pastures deterioration and seasonal fluctuations in pastures productivity and quality affecting animal health and performance (Hamed, 2007). Agro- industrial by- products and browses are important in filling the nutritional gap, especially in the dry season (Mohmed, 2001). It is therefore, important to exploit new feed resources for efficient animal production.